UniTED: A Unified Time Series Event Detection Repository - Lima, Janio; Castro, Hélio; Oliveira, Luiz; Paixão, Ellen; Baroni, Lais; Salles, Rebecca; Vargas, Ricardo; Ogasawara, Eduardo (Anais do Brazilian e-Science Workshop (BreSci); 2025: Anais do XIX Brazilian e-Science Workshop, 2025)
Event detection in time series is essential for numerous real-world applications, from monitoring industrial systems to identifying health anomalies. Public annotated datasets are crucial for benchmarking, training, and validating detection models. Despite recent advances in the field, there is a lack of a standardized and unified repository for evaluating different event types, which limits progress in reproducibility, comparability, and model development. This paper presents the UniTED, a Unified Event Detection Dataset for time series. UniTED consolidates annotated series from diverse domains and offers a common format and protocol for evaluation. The repository supports three event types: anomalies, change points, and motifs. UniTED fosters reusability and reproducibility, contributing to improved performance assessment and model generalization across data analysis tasks. However, existing datasets have limitations, including poor standardization, a lack of annotation guidelines, limited support for different event types, and difficulties in automating performance evaluation. UniTED presents a harmonized ETL process, label and annotation conventions, and an open-source implementation. Three use cases are presented to demonstrate the applicability of the dataset.